Petrus van Mastricht (1630-1706): Reformed orthodoxy : method and piety - Neele, Adriaan Cornelis (Brill's series in church history 1572-4107, 2009)
Introduction -- The life and work of Petrus van Mastricht in the context of his time -- The life of Petrus van Mastricht -- Mastricht's work : the Theoretico-practica theologia -- The premises of the Theoretico-practica theologia -- Prolegomena -- Faith -- A cross-section study of the doctrine of God -- Exegesis -- Doctrine -- Elenctic -- Praxis -- An in-depth study of the doctrine of God -- The structure of the doctrine of God -- The Quid sit deus -- The Holy Trinity -- Conclusion and prospect